PELATIHAN PUBLIC SPEAKING BUJANG GADIS SUNGSANG OLEH PT PLN UIP SUMBAGSEL DALAM MENDUKUNG PENGEMBANGAN DESA WISATA DI SUNGSANG IV BANYUASIN II SUMATERA SELATAN - Nasyaya, Annada; Kholek, Abdul; Simarmata, Marudut J.F.; Anugrah, Erwin C; Zahana, Yui; Akbar, Dinar Tri; Zalyanti, Detia (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Village development is greatly influenced by the active role of youth as enthusiastic, energetic, and creative agents of change. To optimize the contribution of the youth in promoting tourism, preserving culture, improving community welfare, and encouraging village progress through creative and innovative activities. The Bujang Gadis Sungsang (BGS) Association is one of the organizations that is quite active in various youth and tourism activities. However, it is necessary to enhance the capacity and supportive certification for these youth groups to provide a greater contribution to various village tourism development activities. The BGS Public Speaking Training is a strategic step taken by PT PLN UIP Sumbagsel to contribute to community improvement, especially in the field of education. The Public Speaking Training Program organized by PT PLN UIP Sumbagsel in collaboration with the Faculty of Social and Political Sciences Universitas Sriwijaya and Dinamis Nawar Academy (DNA.) Public Speaking has provided understanding to Bujang Gadis Sungsang to help accelerate the development of the tourism village in Sungsang IV. This training has also successfully conducted competency exams for participants, resulting in 12 participants passing the exam and being certified by the National Professional Certification Agency (BNSP) of the Republic of Indonesia, which can be applied in daily life